2020
DOI: 10.1111/jocs.15070
|View full text |Cite
|
Sign up to set email alerts
|

Acute type A aortic dissection in‐hours versus out‐of‐hours: A systematic review and meta‐analysis

Abstract: Objective: We sought to compare clinical outcomes in patients with acute type A aortic dissection that undergone surgical repair during in-hours (IH) versus out-ofhours (OOH). Methods: An electronic literature search was done till March 2020 to include studies with comparative cohorts of IH versus OOH. Primary outcomes were 30-day mortality, stroke, and reoperation for bleeding; secondary outcomes were acute kidney injury, total hospital stay, and intensive care unit stay. Results: Six articles with a total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
3
5
0
Order By: Relevance
“…In our interpretation of recent metaanalysis results, 30-day mortality rate was 26% for in-hours surgery versus 24% for out-of-hours surgery. 7 After sensitivity analysis there was no statistical difference, again corroborating our findings.…”
Section: Time Of the Day Or Surgeon Volume-what Matters Most In Type supporting
confidence: 85%
“…In our interpretation of recent metaanalysis results, 30-day mortality rate was 26% for in-hours surgery versus 24% for out-of-hours surgery. 7 After sensitivity analysis there was no statistical difference, again corroborating our findings.…”
Section: Time Of the Day Or Surgeon Volume-what Matters Most In Type supporting
confidence: 85%
“… 15 Further studies are needed to examine postoperative outcomes following surgery in both in hours and out of hours for ATAAD. 15 , 16 , 17 , 18 Centers should report on the structure of their aortic service and out-of-hours on-call dissection team as well as independent preoperative predictors of mortality as identified on analysis of the IRAD database (eg, history of aortic valve replacement, migrating chest pain, hypotension, shock or tamponade, cardiac tamponade, and limb ischemia). 15 …”
Section: Discussionmentioning
confidence: 99%
“…Our recent meta-analysis 6 showed that operating out-of-hours is associated with higher mortality rates (RR = 0.81; 95% Cl: [0.72, 0.90]; p = .0001). However, a sensitivity analysis has shown no significant difference in mortality rates (RR = 0.83; 95% CI: [0.68, 1.01]; p = .06) and this could reflect the impact of either low volume center not having an appropriate dissection rota or dedicated aortic team.…”
Section: Time Of the Day Or Surgeon Volume-experience Matters Most?mentioning
confidence: 99%